Factor Affecting Consumer Behaviours: The Case of Kellogg's - Wei Leik Keow (Advances in Global Economics and Business Journal, 2023)
The demand for Kellogg' products has increased due to the ease of preparation, one of the characteristics of Kellogg's products. Cereal and breakfast food sales have increased by 4.1% by the end of 2021. As the industry is experiencing progressive growth, Kellogg's, rated one of the world's most valuable food manufacturing brands, must excel in several areas to emerge as the industry leader. This research paper was conducted to investigate the relationship between several independent variables and consumer behaviour. A structured primary online survey of 157 Kellogg's customers was collected through Google Forms. This paper analyses the factors using appropriate statistical tools such as descriptive statistics, regression analysis, and inferential statistics. This study identified that psychological factors, market attributes, and product attributes would affect consumer behaviour directly. This study also delivered practical insights for the company engaging in the production and distribution of breakfast foods in the face of increasing consumer demand for healthy food options.